Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1186/1756-0500-7-589
|View full text |Cite
|
Sign up to set email alerts
|

Activity of crizotinib over choroidal metastases in Non-Small-Cell Lung Cancer (NSCLC)-ALK rearranged: a case report

Abstract: BackgroundAdenocarcinoma of the lung with EML4-ALK translocation is a rare subtype of Non Small-Cell Lung Cancer (NSCLC) that has recently shown to benefit from treatment with crizotinib. Despite the concerns about the efficacy of crizotinib over cerebral metastases, some reports have described its activity, although always after local treatment with radiotherapy. Recently it has been reported activity of crizotinib over choroidal metastases, again after radiotherapy.Case presentationHerein we report a case of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 8 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…There are some studies in the form of more case reports, especially on adenocarcinoma, and it is reported that it responds well to various chemotherapies. In particular, tyrosine kinase inhibitors such as bevacizumab, gefitinib, erlotinib, crizotinib and pemekrexet are more effective chemotherapy drugs in adenocancer (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…There are some studies in the form of more case reports, especially on adenocarcinoma, and it is reported that it responds well to various chemotherapies. In particular, tyrosine kinase inhibitors such as bevacizumab, gefitinib, erlotinib, crizotinib and pemekrexet are more effective chemotherapy drugs in adenocancer (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…She started alectinib treatment and both her ocular and systemic symptoms were palliated in a week. Bearz.A et al.reported the case of a patient with choroidal metastasis in progression in the right lung and mediastinal lymph nodes after 15 months of crizotinib treatment, and then switched to oral aletinib and went into remission after 7 months ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…10 In 2014, the first case of choroidal metastasis responding to crizotinib without previous radiotherapy was reported. 11 Lu et al presented a patient with receptor tyrosine kinase 1-rearranged NSCLC who presented with a choroidal metastasis that did not respond to the initial chemotherapy but had a rapid and complete response to crizotinib. 12 Cui et al report a case that did have an initial response to crizotinib but after 16 months of crizotinib developed resistance with a new choroidal metastasis.…”
Section: Discussionmentioning
confidence: 99%